Rhabdomyolysis and Cardiomyopathy in a 20-Year-Old Patient with CPT II Deficiency - M. Vavlukis; Eftimov, A; Zafirovska, P; Caparovska, E; Pocesta, B; S. Kedev; A. Dimovski (Hindawi Limited, 2014)
Aim. To raise the awareness of adult-onset carnitite palmitoyltransferase II deficiency (CPT II) by describing clinical, biochemical, and genetic features of the disease occurring in early adulthood. Method. Review of the case characteristics and literature review. Results. We report on a 20-year-old man presenting with dyspnea, fatigue, fever, and myoglobinuria. This was the second episode with such symptoms (the previous one being three years earlier). The symptoms occurred after intense physical work, followed by a viral infection resulting in fever treated with NSAIDs. Massive rhabdomyolysis was diagnosed, resulting in acute renal failure necessitating plasmapheresis and hemodialysis, acute hepatic lesion, and respiratory insufficiency. Additionally, our patient had cardiomyopathy with volume overload. After a detailed workup, CPT II deficiency was suspected. We did a sequencing analysis for exons 1, 3, and 4 of the CPT II gene and found that the patient was homozygote for Ser 113 Leu mutation in exon 3 of the CPT II gene. The patient recovery was complete except for the cardiomiopathy with mildly impaired systolic function. Conclusion. Whenever a patient suffers recurrent episodes of myalgia, followed by myoglobinuria due to rhabdomyolysis, we should always consider the possibility of this rare condition. The definitive diagnose of this condition is achieved by genetic testing.
Keywords: rhabdomyolysis; cardiomyopathy; CPT II Deficiency